2293. Evaluation of Three Rapid Molecular Assays for the Detection of Group A Streptococcus. (26th November 2018) - Beck, Eric; Ross, Patricia; Clow, Ashlee; Larson, Jennifer; Patel, Prina; Siason, Sarah; Drozd, Matthew; Patel, Pankaj; Costello, Michael
Abstract: Background: Group A Streptococcus (GAS), the primary causative agent of bacterial pharyngitis, is most commonly diagnosed with a rapid antigen test performed at the point of care followed by bacterial culture, if negative. Final test results may not be available for 24–72 hours, which can delay the time to therapy and cause patients to miss additional work or school days. Recently, rapid molecular tests, including some that are CLIA-waived, have become available allowing providers to obtain results within a timeframe similar to rapid antigen tests, but with accuracies comparable to traditional culture. The purpose of this study was to evaluate the performance of the Alere™i Strep A test, Roche cobas® Strep A test, and the Cepheid Xpert Xpress Strep A Test (RUO Version) compared with the OSOM Group A Streptococcus rapid antigen test and traditional bacterial culture. All molecular tests are either currently or in the process of obtaining CLIA-Waived status and can be completed in less than 25 minutes. Methods: The current testing process in our healthcare system (AdvocateAuroraHealth) is to collect oropharyngeal swabs with both a traditional swab and an ESwab (Copan). The traditional swab is used for rapid antigen testing and the ESwab is submitted to the microbiology laboratory for bacterial culture, if indicated. Residual ESwab specimens were de-identified, cultured, and tested using the Alere and Roche molecular assays (at the time of de-identification the result of the GAS rapid antigen test that was performed on the same patient at the time of ESwab collection was noted). Following testing, ESwab specimens were frozen and tested on the Cepheid molecular assay within 6 months. In total 194 specimens were compared. Results: Specimens positive by culture or in two of three molecular assays were considered true positives. The results can be seen in the Table below. Conclusion: All molecular tests were more sensitive than antigen testing and culture and could be completed in a timeframe similar to the rapid antigen test. Replacing traditional GAS diagnosis with rapid GAS molecular assays will allow providers to make definitive clinical decisions in near real-time. Acknowledgements. Molecular testing reagents and equipment were provided by Roche, Alere, and Cepheid. Disclosures: All authors: No reported disclosures.